A study on DPL model of heat transfer in bi-layer tissues during MFH treatment. (1st August 2016) - Kumar, Dinesh; Kumar, P.; Rai, K.N.
Abstract: In this paper, dual-phase-lag bioheat transfer model subjected to Fourier and non-Fourier boundary conditions for bi-layer tissues has been solved using finite element Legendre wavelet Galerkin method (FELWGM) during magnetic fluid hyperthermia. FELWGM localizes small scale variation of solution and fast switching of functional bases. It has been observed that moderate hyperthermia temperature range (41–46 °C) can be better achieved in spherical symmetric coordinate system and treatment method will be independent of the Fourier and non-Fourier boundary conditions used. The effect of phase-lag times has been observed only in tumor region. FCC FePt magnetic nano-particle produces more effective treatment with respect to other magnetic nano-particles. The effect of variability of magnetic heat source parameters (magnetic induction, frequency, diameter of magnetic nano-particles, volume fractional of magnetic nano-particles and ligand layer thickness) has been investigated. The physical property of these parameters has been described in detail during magnetic fluid hyperthermia (MFH) treatment and also discussed the clinical application of MFH in Oncology. Abstract : Highlights: DPL bioheat model for bi-layer tissues has been studied for MFH treatment. Fourier and non-Fourier boundary conditions are considered at outer surface r = L . FELWGM is used for solution of DPL bioheat model. Magnetic nanoparticles are injected at the center of tumor.